Reconfigured Professional Purpose in Times of Crisis: Experiences of Frontline Healthcare Professionals During the Covid-19 Pandemic - Perez-Arrau, J (Elsevier Ltd, 2023)
How is professional purpose impacted in the context of a crisis? Building on discussions about professional purpose and identity, the paper explores how the understanding that professionals have about the framing, scope of functioning and aims of their profession is impacted during a time of crisis. The paper draws on interviews with 41 kinesiologists working at an accidents & emergencies (A&E) hospital in Chile during the COVID-19 pandemic. The paper shows professional purpose as a fluid, situated notion that gets re-shaped in light of contextual features. In the face of new and changing demands during times of crisis, professionals reconfigure their professional purpose to take advantage of the opportunities available. This reconfiguration takes place in response to the external context of the profession (its positioning in the public domain) and the internal relational context of the profession (its positioning with other professionals). The paper suggests a research agenda to develop a processual, situated approach to the interrogation of professional purpose to embed contextual features in scholarship in this area. © 2023 The Authors
Keywords: Professional purpose; Frontline healthcare professionals; Kinesiologists; COVID-19 pandemic; Crisis